2012
DOI: 10.1590/s0037-86822012000500009
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis case series with and without central nervous system involvement

Abstract: Introduction: Paracoccidioidomycosis (PCM) is the most important systemic mycosis in South America. Central nervous system involvement is potentially fatal and can occur in 12.5% of cases. This paper aims to contribute to the literature describing eight cases of neuroparacoccidioidomycosis (NPMC) and compare their characteristics with patients without neurological involvement, to identify unique characteristics of NPCM. Methods: A cohort of 213 PCM cases was evaluated at the Infectious Diseases Clinic of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
3
17
0
1
Order By: Relevance
“…In the current study, the predominance of NPCM in men was 13/1, and is in accordance with previous reports 7,11,20,[29][30][31] . In some studies, NPCM occurred exclusively in men 10,32 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, the predominance of NPCM in men was 13/1, and is in accordance with previous reports 7,11,20,[29][30][31] . In some studies, NPCM occurred exclusively in men 10,32 .…”
Section: Discussionsupporting
confidence: 93%
“…Soil is the main natural source for infectious airborne conidia and people living in rural areas are the main population at risk 8 . In this study, occupational activity related to soil was present in 58% of cases, in accordance with previous reports 10,20,[30][31][32]35,36 although this information could be underestimated due to lack of appropriate investigation during anamnesis. Occasional non-autochthonous cases of PCM have been reported outside Latin America 37 .…”
Section: Discussionsupporting
confidence: 92%
“…Multiple parenchymal lesions accounts for 23-75% of cases and the number of lesions ranges from 1 to 10. [1][2][3]5,6,8,9,13,15,16 Leptomeningeal and/or pachymeningeal involvement represent the meningeal presentation, and it manifests by meningeal signs. Spinal cord involvement is rare and accounts for 0.6% of all cases of PCM and 4% of NPCM.…”
Section: Discussionmentioning
confidence: 99%
“…48 A cohort study with 213 consecutive PCM cases, with systematic search for SNC involvement, demonstrated a prevalence of 3.8% of specific lesions, with all cases presenting parenchymal location and other findings in accordance to the literature. 49 …”
Section: Clinical Presentationmentioning
confidence: 99%